Bob Dylan : American troubadour - Brown, Donald, 1959- (Tempo (Lanham, Md.), 2014)
In Bob Dylan: American Troubadour, Donald Brown follows the shifting versions of Dylan, from his songs of conscientious social involvement to more personal exploratory songs; from his influential rock albums of the mid-'60s to his adaptations of Country music; from his three very different tours in the 1970s to his "born again" period as a proselytizer for Christ, to his frustrations as a recording and performing artist in the 1980s; from his retrospective importance in the Nineties to the refreshingly vital albums he has been producing in the 21st century